Review: Mitogen-Activated Protein Kinases in nutritional signaling in Arabidopsis. (July 2017) - Chardin, Camille; Schenk, Sebastian T.; Hirt, Heribert; Colcombet, Jean; Krapp, Anne
Highlights: Mitogen-Activated Protein Kinases cascades are part of many signaling pathways. MAPKs might act as central hubs integrating multiple signals. Expression of a subclass of MAPKs is modified in response to nutritional variation. New evidences for the role of MAPKs in nutritional signaling are now emerging. Abstract: Mitogen-Activated Protein Kinase (MAPK) cascades are functional modules widespread among eukaryotic organisms. In plants, these modules are encoded by large multigenic families and are involved in many biological processes ranging from stress responses to cellular differentiation and organ development. Furthermore, MAPK pathways are involved in the perception of environmental and physiological modifications. Interestingly, some MAPKs play a role in several signaling networks and could have an integrative function for the response of plants to their environment. In this review, we describe the classification of MAPKs and highlight some of their biochemical actions. We performed an in silico analysis of MAPK gene expression in response to nutrients supporting their involvement in nutritional signaling. While several MAPKs have been identified as players in sugar, nitrogen, phosphate, iron and potassium-related signaling pathways, their biochemical functions are yet mainly unknown. The integration of these regulatory cascades in the current understanding of nutrient signaling is discussed and potential new avenues for approaches toward plants with higher nutrient use efficiencies are evoked.